Functional and comparative characterization of Saccharomyces cerevisiae RVB1 and RVB2 genes with bacterial Ruv homologues - Radovic, Slobodanka (2007)
Expression of yeast RuvB-like gene analogues of bacterial RuvB is self-regulated, as episomal overexpression of RVB1 and RVB2 decreases the expression of their chromosomal copies by 85%. Heterozygosity for either gene correlates with lower double-strand break repair of inverted-repeat DNA and decreased survival after UV irradiation, suggesting their haploinsufficiency, while overexpression of the bacterial RuvAB complex improves UV survival in yeast. Rvb2p preferentially binds artificial DNA Holiday junctions like the bacterial RuvAB complex, whereas Rvb1p binds to duplex or cruciform DNA. As both proteins also interact with chromatin, their role in recombination and repair through chromatin remodelling, and their evolutionary relationship to the bacterial homologue, is discussed.